Study of crack resistance of TiAlN coatings by scratch testing; Physical Mesomechanics; Vol. 20, iss. 2 - Shugurov A. R. Artur Rubinovich; Akulinkin A. A. Aleksandr Aleksandrovich; Panin A. V. Alexey Viktorovich; Sergeev V. P. Viktor Petrovich; Kalashnikov M. P. Mark Petrovich; Voronov A. V. Andrey Viktorovich; Cheng Chin-Hsiang (2017, 2017)
Title screen